Obstacles of Educational Supervision in the Province of Kerbala as Seen by Educational Supervisors - Diaa Saleh Mahdi Al-Attar (Journal of Global Pharma Technology, 2018)
The main objective of this research is to identify the most common obstacles facing educational supervision in Karbala Governorate. The research community has identified a number of educational supervisors in Karbala Education Directorate. A sample of (90) supervisors and supervisors were selected. To complete the research, a questionnaire was prepared (45) items distributed on five axes, and indicated the search results to the physical and administrative obstacles that limit the effectiveness of supervisory practices and a high degree, and that teachers look passively supervisors greatly affect so that should be changed because the supervisors' colleagues to achieve the goals of practical education.Keywords: Obstacles and educational supervision.